Effects of azathioprine on response of renal anaemia to subcutaneous recombinant human erythropoietin. Issue 1 (January 1993) - Howarth, J E; Waters, H M; Shanks, D; Hyde, K; Yin, J A; Geary, C G; Anastassiades, E; Howarth, D; Gokal, R
Abstract : AIMS: To determine the effect of concomitant azathioprine treatment on the response of patients with renal failure to treatment with subcutaneous recombinant human erythropoietin (r-HuEPO). METHODS: Two groups of patients with renal failure not receiving haemodialysis were studied. One comprised seven patients receiving erythropoietin alone, the second consisted of nine patients who were also treated with azathioprine. The haematological changes were monitored, and the functional erythropoietic response was studied by two different ferrokinetic models. One analysed the initial, the other the extended plasma iron clearance. Studies were performed before r-HuEPO treatment on all 16 patients, and repeated on 11 of these when the target haemoglobin (10-11 g/dl) was achieved and stabilised. Total erythropoiesis was determined using both techniques. Analysis of the extended plasma iron clearance also permitted calculation of both effective and ineffective erythroid activity. RESULTS: The haematological response to r-HuEPO was the same for both patient groups. Measurement of total erythropoiesis by both ferrokinetic methods showed good correlation. For those receiving long term azathioprine, the percentage ineffective erythropoiesis was high compared with that of the other patients, and remained so for as long as they continued with azathioprine. For those uncomplicated by azathioprine treatment, r-HuEPO increased levels of both effective and ineffective erythropoiesis by the same degree. A substantial reduction in ineffective erythropoiesis was shown only by those patients who either discontinued or reduced their azathioprine once they started r-HuEPO treatment. CONCLUSIONS: Azathioprine increases ineffective erythropoiesis. In this study, the r-HuEPO dose was sufficient to overcome this effect and promoted effective erythropoiesis so that the anaemia lessened. Measurement of total erythropoiesis provided limited information on the functional changes involved, differentiation of effective from ineffective erythropoiesis being necessary to define the changes after azathioprine reduction or withdrawal.